095. A Rare Case Report: A 10-Years-Old Girl with Ectopic Ureter and Ectopic Hypoplasia Kidney - Saputro, Johan Eko; Addin, Sofyan Rais (JBN (Jurnal Bedah Nasional), 2024)
Background : The urinary tract system develops from an embryological structure in the dorsal part of the embryo, the intermediate mesoderm, which develops between the 4th and 10th week of gestation. During the embryogenesis process, disturbed metanephric mesenchyme can cause congenital abnormalities of the kidneys and urinary tract (CAKUT), one of which is ectopic abnormalities. Ectopic ureter and ectopic kidney had an incidence of 1:2000 and 1:3000 worldwide, respectively. Additionally, this rare case will be even more uncommon with the presence of a hypoplasia kidney. These anomalies contribute to impaired urinary drainage. Case : A 10-year-old girl was referred to the surgical department at Dr. Kariadi Hospital due to continuous urinary incontinence. She can urinate regularly via the urethra, but constantly has vaginal leaks. Previously, she had physiotherapy at the regional hospital but there was no improvement. Contrast-enhanced computed tomography revealed an ectopic kidney image accompanied by right kidney hypoplasia and a cyst on the upper pole of the right kidney measuring ± 0.89 x 0.86 cm. Then, urethrocystoscopy and colposcopy also showed the right ureteral orifice on the superior wall of the vagina, ± 2 cm from the vaginal introitus with the left ureteral orifice in a normal position. The patient underwent ureteral reimplantation, and her symptoms successfully resolved, leading to a favourable prognosis. Conclusion : Complete ectopic ureter and ectopic hypoplasia kidney are rare congenital anomalies that require early recognition and careful management in pediatric patients.